2009
DOI: 10.1002/pmic.200800882
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of human papillomavirus‐related oral squamous cell carcinoma: Identification of thioredoxin and epidermal‐fatty acid binding protein as upregulated protein markers in microdissected tumor tissue

Abstract: Human papillomavirus (HPV) infection has been identified as an etiologic agent for a subset of oral squamous cell carcinoma (OSCC) with increasing incidence. HPV DNA-positivity may confer better prognosis but the related oncogenic mechanisms are unknown. For the identification of HPV relevant proteins, we analyzed microdissected cells from HPV DNA-positive (n = 17) and HPV DNA-negative (n = 7) OSCC tissue samples. We identified 18 proteins from tumor tissues by peptide fingerprint mapping and SELDI MS that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…FABP5 (E-FAPB) is upregulated by the tumor-associated antigen EpCAM in HNSCC,(43) while proteomic analysis of HPV-related HNSCCs revealed that FABP5 was one of the proteins upregluated in these tumors. (44) One of the proteins with lower spectral counts in HNSCC was GBP6. The presumed function of this protein is to bind guanylate and to hydrolyze GTP to both GDP and GMP but no data is available for this specific for of GBP.…”
Section: Resultsmentioning
confidence: 99%
“…FABP5 (E-FAPB) is upregulated by the tumor-associated antigen EpCAM in HNSCC,(43) while proteomic analysis of HPV-related HNSCCs revealed that FABP5 was one of the proteins upregluated in these tumors. (44) One of the proteins with lower spectral counts in HNSCC was GBP6. The presumed function of this protein is to bind guanylate and to hydrolyze GTP to both GDP and GMP but no data is available for this specific for of GBP.…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acid binding protein 5 (psoriasis-associated, FABP5), found in epidermal cells, was first identified to be up-regulated in psoriasis keratinocytes [34]. In cancer cells, FABP5 increases cell proliferation and invasiveness, as recently demonstrated in oral squamous cell carcinoma [35] where its expression may be HPV-related [36]. In non-cancer keratinocytes FABP5 elevation may be necessary for the activation of cell motility during epidermal wound healing [37].…”
Section: Discussionmentioning
confidence: 99%
“…Thioredoxin (TRX) and epidermal fatty acid binding protein (E-FABP) were identified by proteomics to be upregulated in HPV-related tumors [22]. TRX is a redox mediator promoting cell survival, e.g., under hypoxic conditions and oxidative stress.…”
Section: Protein Expression Alterationsmentioning
confidence: 99%